Ubi boni ibi patria - Boccasile, Francesco (Lexis, 2022)
A historical and literary reassessment of fr. Stob. 4.29c.53, well-known as regards the Theognis-question, is offered with the aim to put it in the Socratic context; in addition, Xenophon’s authorship is reaffirmed. In order to shed light on the authorship and authenticity of the text, a re-examination of its language and style is also undertaken.